2007
DOI: 10.1158/0008-5472.can-07-0327
|View full text |Cite
|
Sign up to set email alerts
|

Taxol Increases the Amount and T Cell–Activating Ability of Self-Immune Stimulatory Multimolecular Complexes Found in Ovarian Cancer Cells

Abstract: It has been proposed that chemotherapy enhances tumor antigen (TA)-specific immunity. The molecular form of TA from ovarian tumor that activates cellular immunity is unknown. We report here identification of a novel molecular form of immunogenic TA for CD8 + cells named self-immune stimulatory multimolecular complexes (ISMMC). ISMMC consist of a molecular complex of polyosome/ribosome-bound ubiquitinated nascent HER-2 polypeptides. This complex is chaperoned by heat shock protein Gp96, which mediates ISMMC upt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The presence of high numbers of intraepithelial, but not stromal, CD8-positive T lymphocytes was of uni-and multivariate prognostic benefit for stage III ovarian cancer patients, especially in the large subgroup of patients receiving adjuvant paclitaxel/carboplatin therapy. Interestingly, Tsuda et al, 2007 showed that Taxol stimulates the immunogenic potential of CD8-positive T cells in vitro, an effect that may be further exploited in current therapeutic studies (Disis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of high numbers of intraepithelial, but not stromal, CD8-positive T lymphocytes was of uni-and multivariate prognostic benefit for stage III ovarian cancer patients, especially in the large subgroup of patients receiving adjuvant paclitaxel/carboplatin therapy. Interestingly, Tsuda et al, 2007 showed that Taxol stimulates the immunogenic potential of CD8-positive T cells in vitro, an effect that may be further exploited in current therapeutic studies (Disis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A greater influx of tumor-infiltrating lymphocytes in breast cancer tumors has been correlated with a better response to chemotherapy 59,61. Paclitaxel may be a particularly strong immunostimulant, as it is able to both activate CD8 + T cells and reduce immunosuppressive cells, such as regulatory T cells 62,63. Docetaxel has been shown to increase CD8 + T-cell production of IFNγ (a stimulator of tumor-cell killing), but docetaxel does not appear to inhibit the suppressor function of regulatory T cells 64.…”
Section: Chemotherapy In Combination With Checkpoint Inhibitorsmentioning
confidence: 99%
“…If chemotherapy drugs have been designed to induce tumor cell death, 11 they also can boost or hamper protective immune responses by modifying the composition and function of the tumor immune contexture. [11][12][13][14] The aim of the present study was to characterize the tumor and immune compartments of NSCLC patients treated with neoadjuvant chemotherapy and evaluate their association with clinical outcome.…”
Section: Introductionmentioning
confidence: 99%